IMPLEMENTATION OF FULL-DAY SCHOOL PROGRAM IN STIMULATING THE INDEPENDENCE OF 5-6-YEAR-OLD CHILDREN AT TK AL MUSLIM - Suryani, Lilis; Aulia, Rachmasari (FORUM PAEDAGOGIK, 2024)
The research aims to describe the sub-focus: the implementation of the full-day school program at Al Muslim Kindergarten in stimulating children's independence, the obstacles and solutions in implementing the full-day school program, the impact of the full-day school program on children's independence development, and parental involvement. This research uses a descriptive qualitative approach. Research subjects: the principal, teachers, students, and parents of Kindergarten B Khalid. Data collection techniques include observation, interviews, and documentation. Data analysis uses an interactive model. The research findings indicate that the implementation of the full day school program at Al Muslim Kindergarten features a comprehensive curriculum, including religious education (Tilawati, Tahfizh, prayer habits, daily prayers), habituation programs, and specialized programs; teachers have the flexibility in classroom management, and the entire school community actively participates in fostering children's independence, supported by adequate facilities; the challenges faced include insufficient parental support for the school program; the positive impacts of the full day program on children include the establishment of positive habits, getting used to activities according to their schedule, becoming more independent in taking care of themselves, being able to express their needs, taking more responsibility for their activities, being more creative and proactive, easily socializing, being disciplined, better able to respect others, more confident, and willing to perform in front of many people; the role of parents includes the obligation to understand the school program and to reinforce positive habits at home.